A 1-year follow-up of a randomized clinical trial with focus on manual and electric toothbrushes' effect on dental hygiene in nursing homes. (19th May 2018) - Fjeld, Katrine Gahre; Eide, Hilde; Mowe, Morten; Sandvik, Leiv; Willumsen, Tiril
Abstract: Objective: A 2-month randomized clinical trial (RCT) study comparing electric and manual toothbrushes used by residents in nursing homes showed significant reduction in plaque score for both groups. The aim of this follow up study was to study if the effect sustained in a longer perspective when toothbrushes were used according to resident's own preference. Materials and methods: One year after baseline of the RCT-study, 100 participants were re-examined. The simplified oral hygiene index (OHI-S) was used as outcome measure on dental plaque. Results : The mean age was 86.6, 78.1% had three or more medical diagnoses and 52.2% had moderate to severe cognitive impairment. The mean number of natural teeth was 18.8. After 1 year, mean plaque scores was significantly reduced within the population, from 1.2 to 0.7 ( p  < .001). A total of 46 participants preferred to use an electric toothbrush and 54 preferred manual. No significant difference in plaque score was found between electric and manual toothbrushes. Conclusion: After 1 year, the improvement in dental hygiene from the RCT study sustained for users of both electric and manual toothbrush. Focus upon tooth brushing seems to be efficient and both manual and electric toothbrushes should be available in nursing homes.